(3OQGSGJ aj LZQGajI GdJfejI (B/s - (3GdaGVdi, eMeO Ydi HgLJs; (3GdMeGOj, eMeO YHO GdMejO s ((3GdGScfOQjI(B: s (3efTCI GdeYGQa(B, s, 1996)
(3efgL YGe dOQGSI bQGFf GdJNda,GdNUGFU GdHTQjI hGdGLJeGYjI,YOe GdJhGRf GdGbJUGOj,GdJfejI hGdGSJbdGds
(3HHdjhZQGajG(B:(3U(B.307s
Keywords: (3GdLZQGajG GdGbJUGOjIs